The law's universal condemning and enslaving power: reading Paul, the Old Testament, and Second Temple Jewish literature - Blazosky, Bryan (Bulletin for Biblical Research Supplement, 2019)
Frontmatter -- Contents -- Tables -- Acknowledgments -- Abbreviations -- Introduction -- Chapter 1. The Torah -- Chapter 2. The Prophets and the Writings -- Chapter 3. The Second Temple Jewish Literature -- Chapter 4. Galatians -- Chapter 5. Romans -- Chapter 6. 1 Corinthians and the Disputed Pauline Epistles -- Bibliography -- Index of Authors -- Index of Scripture -- Bulletin for Biblical Research Supplements